Effects of thyroxin and donepezil on hippocampal acetylcholine content and syntaxin-1 and munc-18 expression in adult rats with hypothyroidism - WANG, NAN (D.A. Spandidos, 2014)
Adult-onset hypothyroidism induces various impairments in hippocampus-dependent cognitive function, in which numerous synaptic proteins and neurotransmitters are involved. Donepezil (DON), an acetylcholinesterase inhibitor, has been shown to be efficient in improving cognitive function. The aim of the present study was to investigate the effects of adult-onset hypothyroidism on the expression levels of the synaptic proteins syntaxin-1 and munc-18, as well as the content of the neurotransmitter acetylcholine (ACh) in the hippocampus. In addition, the study explored the effects of thyroxin (T4) and DON treatment on the altered parameters. The study involved 55 Sprague-Dawley rats that were randomly divided into five groups: Control, hypothyroid (0.05% 6-n-propyl-2-thiouracil; added to the drinking water), hypothyroid treated with T4 (6 μg/100 g body weight once daily; intraperitoneal injection), hypothyroid treated with DON (0.005%; added to the drinking water) and hypothyroid treated with a combination of the two drugs (6 μg/100 g T4 and 0.005% DON). The concentration of ACh was determined in the homogenized hippocampus of each animal by alkaline hydroxylamine colorimetry. The protein levels of syntaxin-1 and munc-18 were determined by immunohistochemistry. The results showed that the content of ACh in the hippocampi of the hypothyroid rats was significantly decreased compared with that in the controls and that T4 monotherapy and DON administration restored the ACh content to normal values. In the hippocampi of the hypothyroid group, munc-18 was expressed at significantly lower levels, while the expression levels of syntaxin-1 were increased compared with the levels in the control group. Treatment with T4 alone restored the expression of syntaxin-1 but failed to normalize munc-18 expression levels. The co-administration of T4 and DON returned the munc-18 levels to normal values. These observations indicate that adult-onset hypothyroidism induces alterations in the levels of munc-18, syntaxin-1 and ACh in the hippocampus. Syntaxin-1 and ACh levels were restored by T4 monotherapy while munc-18 levels were not. In addition, the co-administration of T4 and DON resulted in more effective restoration than either alone. The thyroid hormone has a direct effect on metabolism of hippocampal ACh in adult rats and DON is helpful for treatment of synaptic protein impairment induced by hypothyroidism.